Answer: To find the equation of the ellipse, we need to use the standard form equation of an ellipse:
$\frac{(x-h)^2}{a^2}+\frac{(y-k)^2}{b^2}=1$
where (h,k) is the center of the ellipse, a is the distance from the center to the vertices (the major axis), and b is the distance from the center to the co-vertices (the minor axis).
First, let's find the center of the ellipse. The center of the ellipse is the midpoint of the line segment joining the vertices (-5,1) and (-1,1). Using the midpoint formula, we get:
$(h,k) = \left(\frac{-5+(-1)}{2}, 1\right) = (-3,1)$
Now, we need to find the values of a and b. Since the distance between the vertices is 2a, we have:
$2a = |-5-(-1)| = 4$
So, $a = 2$.
Similarly, the distance between the co-vertices is 2b, we have:
$2b = |2-0| = 2$
So, $b = 1$.
Now, we have all the values we need to write the equation of the ellipse:
$\frac{(x+3)^2}{2^2}+\frac{(y-1)^2}{1^2}=1$
Simplifying this equation, we get:
$\frac{(x+3)^2}{4}+(y-1)^2=1$
So, the equation of the ellipse is:
$(x+3)^2/4 + (y-1)^2/1 = 1$
Explanation: